De la sala de prensa al teletrabajo. La cobertura periodística durante la emergencia sanitaria del covid 19 - Garcia Benitez, Jeniffer Vanessa (2021)
This case study is based on the collection of information on how teleworking was used for social communicators during the pandemic that arose in 2020, how the information that would be transmitted through this tool was corroborated. The methods and techniques used for this case study were the qualitative research method and for data collection it was through the observation sheet. Faced with the pandemic, the media’s task is to report everything that happened in the streets of the country, they play an important role as a means of transmitting information, such as the precaucione that should be taken, what was allowed and what No, how the authorities were acting and what measures were being taken to control what was happening, but not only was the purpose of informing about the virus but also all information in general, both national and international, to be able to give all these details about the confinement they had to go from being in a press room to using telecommuting. One of the problems that this encompasses is the misinformation that was carried out in times of crisis, social communicators had the task of verifying all data they would obtain about what happened in times of pandemic, due to confinement and not being able to move to certain places to corroborate the information on many occasions it was not possible to contrast the information disseminated in other alternative media, which generated difficulties.